2004
DOI: 10.1124/jpet.104.072785
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Hepatic Lipid Homeostasis in Mice after Amiodarone Treatment Is Associated with Peroxisome Proliferator-Activated Receptor-αTarget Gene Activation

Abstract: Amiodarone, an efficacious and widely used antiarrhythmic agent, has been reported to cause hepatotoxicity in some patients. To gain insight into the mechanism of this unwanted effect, mice were administered various doses of amiodarone and examined for changes in hepatic histology and gene regulation. Amiodarone induced hepatomegaly, hepatocyte microvesicular lipid accumulation, and a significant decrease in serum triglycerides and glucose. Northern blot analysis of hepatic RNA revealed a dose-dependent increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 36 publications
(45 reference statements)
3
29
0
Order By: Relevance
“…Interestingly, AM had small PC 1 values, while near zero in PC 2. This result is supported by previous reports that AM induces the expression of PPARα target genes (McCarthy et al, 2004) and lowers serum TH level (De Sandro et al, 1991). Thus, these two directions might have been balanced in the case of the plasma TG reduction by AM.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, AM had small PC 1 values, while near zero in PC 2. This result is supported by previous reports that AM induces the expression of PPARα target genes (McCarthy et al, 2004) and lowers serum TH level (De Sandro et al, 1991). Thus, these two directions might have been balanced in the case of the plasma TG reduction by AM.…”
Section: Discussionsupporting
confidence: 89%
“…It has already been reported that the hepatotoxicity of some drugs is associated with the metabolic activation mediated by CYP3A4. The major metabolite of amiodarone, desethylamiodarone, was reported to cause cytotoxicity in HepG2 cells and rat hepatocytes at lower concentrations than the parent drug amiodarone (McCarthy et al, 2004). Desethylamiodarone is produced mainly by CYP3A4 and by CYP2C8 in humans (Ohyama et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Of the genes regulated by the above transcription factors, there were SCD, FADS, and fatty acid elongation-related (ELOVL6) genes, as well as glycerolipid biosynthesis-related gene (GPAM), and lipogenesis and beta oxidation of lipidrelated genes (CPT1 and 2). AD has been reported to inhibit the hepatic mitochondrial N-oxidation of fatty acids, resulting in an increase in hepatic triglyceride accumulation and a decrease in the hepatic secretion of triglycerides into the blood (McCarthy et al, 2004), as well as in microvesicular steatosis of the liver (Fromenty et al, 1990). AD has been also reported to induce hypercholesterolemia associated with a decrease in liver LDL receptor mRNA (Hudig et al, 1994).…”
Section: Figmentioning
confidence: 99%